Effects of exercise dosage on children with autism spectrum disorder: a systematic review and meta-analysis of randomized controlled trials - Hu, Baojian; Liang, Qingxia; Jiang, Huiyi (Frontiers in Child and Adolescent Psychiatry, 2025)
ObjectiveTo investigate the effects of exercise doses recommended by the American College of Sports Medicine (ACSM) on motor skills, social interaction, behavioral patterns, and verbal and non-verbal communication domains in children with autism.MethodsA systematic search was conducted across PubMed, Embase, Web of Science, and the Cochrane Library, focusing on the effects of physical activity on children with autism. Randomized controlled trials comparing exercise interventions with no intervention were included, and changes in motor skills, social interaction, behavioral patterns,and communication domains were assessed using standardized mean differences (SMD), 95% confidence intervals (CI), and p-values (p < 0.05).Interventions were categorized based on high or low adherence to exercise prescriptions developed or recommended by ACSM.Studies in which ≥70% of components met ACSM criteria were classified as having high adherence, while those with <70% were classified as having low adherence, based on thresholds established in previous literature. A fixed-effects or random-effects model was applied for meta-analysis, and subgroup comparisons were conducted.ResultsA total of 27 studies (29 exercise interventions) involving 1,012 participants were included. In the motor skills domain,the pooled standardized mean difference (SMD) was 1.35, 95% confidence interval (CI) [0.66,2.03]. Subgroup analysis revealed that the high-adherence group showed an SMD of 1.44, 95% CI [0.51,2.36], while the low-adherence group showed an SMD of 1.26, 95% CI [0.15,2.36]. For the social interaction domain,the overall SMD was −0.22, 95% CI [−0.54,0.99]. The high-adherence subgroup had an SMD of −0.41, 95% CI [−0.62,−0.21], whereas the low-adherence group had an SMD of 0.42, 95% CI [−0.50,1.33]. In the behavioral patterns domain, the overall SMD was −0.79, 95% CI [−1.26,−0.32]. Subgroup analysis indicated an SMD of −0.42, 95% CI [−0.73,−0.11] for the high-adherence group and −2.79, 95% CI [−5.63,0.06] for the low-adherence group.For the verbal and non-verbal communication domain, the overall SMD was 0.33, 95% CI [−0.31,0.97]. Subgroup SMD were 0.21,95% CI [−0.14,0.57] for the high-adherence group and 0.59, 95% CI [−1.67,2.84] for the low-adherence group.ConclusionExercise interventions had a significant positive impact on motor skills and behavioral patterns in children with autism spectrum disorder (ASD). Interventions with high adherence to ACSM-recommended exercise dosages were more effective in improving motor skills, social interaction,and behavioral patterns compared to low-adherence dosages.Future evidence-based exercise prescriptions may be established for children with ASD, optimizing motor-functional outcomes.Systematic Review RegistrationPROSPERO, identifier (CRD42024565241).